Attitudes of Slovenian Language Users Towards General Monolingual Dictionaries: an International Perspective - Iztok Kosem; Sascha Wolfer; Robert Lew; Carolin Müller-Spitzer (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
This paper presents the results of a survey on dictionary use in Europe, the largest survey of dictionary use to date with nearly 10,000 participants in nearly thirty countries. The paper focuses on the comparison of the results of the Slovenian participants with the results of the participants from other European countries. The comparisons are made both with the European averages, and with the results from individual countries, in order to determine in which aspects Slovenian participants share similarities with other dictionary users (and non-users) around Europe, and in which aspects they differ. The findings show that in many ways the Slovenian users are similar to their European counterparts, with some noticeable exceptions, including (much) stronger preference for digital dictionaries over print ones, above-average reliance on other people when dictionary does not contain the relevant information, and the largest difference between the price of a dictionary and the amount willing to spend on it.